Development of Static Postural Control: Regulating the Center of Pressure Trajectory - Parvin Kamali Bakhtiar; Azadian, Elaheh; Mahdi Majlesi; Alfonso Delgado-Bonal; Rezaie, MohammadReza (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Studying the developmental process, it may be possible to examine the role of sensory and cognitive systems involved in postural control. The aim of this study was to evaluate static postural control in both linear and nonlinear methods in children aged 7 to 12 years and compare them with young-adult. Materials and Methods: The center of pressure (COP) in eight postural task was assessed in 420 girls and boys 7 to 12 years old and 20 young adults. The linear method included sway, deviation, the amplitude of CoP and velocity. To characterize the nonlinear evaluation, sample entropy (SampEn) was measured. Results: The results showed that 7 and 8-year-old have the most sway, amplitude, speed of CoP and deviations than others (p< 0.05) and adults had the lowest amount. But the SampEn, decreases significantly with age (p< 0.01). The base of support was greater effect on linear and nonlinear than that other conditions, especially in children (p< 0.001). The closed-eyes condition, were not aligned in linear and non-linear evaluation (p< 0.001). Conclusion: The differences between age groups were significant in the challenging situation than that stable condition, due to changes in postural control strategies. Task demands did not have a significant effect on balance variability in adults, but it did affect children and linear variables.